Optimalisasi Lingkungan Sekolah Sebagai Pendukung Motivasi Belajar Siswa di MA Al-Khoziny - Moch Rijalul Amin AZ; Masfufah (EduInovasi: Journal of Basic Educational Studies, 2025)
Improving the quality of education in Indonesia requires schools to continue to optimize the whole potential of the learning environment as an effort to support student motivation and learning outcomes. The conducive learning environment has proven to be one of the important factors that influences intellectual development, creativity, and student motivation. This study aims to describe the management of the learning environment and its relationship with students’ learning motivation at MA Al-Khoziny. Employing a qualitative approach with phenomenological methods, data were collected through participatory observation and structured interviews with teachers and students during the even semester of the 2024–2025 academic year. The results show that a conducive learning environment—physically, socially, and psychologically—plays a crucial role in enhancing students’ learning motivation. Classroom management, the availability of facilities, and positive interactions between teachers and students have a significant positive impact on learning quality. These findings emphasize that optimizing the learning environment in madrasahs should be a priority to support the improvement of student motivation and learning outcomes.